Pest categorisation of Stagonosporopsis andigena - Bragard, Claude (John Wiley and Sons Inc., 2018)

(untitled) (EFSA J)
The Panel on Plant Health performed a pest categorisation of Stagonosporopsis andigena, the causal agent of black blight of potato, for the EU. The pest is a well‐defined fungal species and reliable methods exist for its detection and identification. S. andigena is present in Bolivia and Peru. The pest is not known to occur in the EU and is listed in Annex IAI of Directive 2000/29/EC as Phoma andina, meaning its introduction into the EU is prohibited. The major cultivated host is Solanum tuberosum (potato); other tuber‐forming Solanum species and wild solanaceous plants are also affected. All hosts and pathways of entry of the pest into the EU are currently regulated. Host availability and climate matching suggest that S. andigena could establish in parts of the EU and further spread mainly by human‐assisted means. The pest affects leaves, stems and petioles of potato plants causing lesions and premature leaf drop but not the underground parts, including tubers. The disease causes yield reductions up to 80%, depending on the susceptibility of potato cultivars. Early application of fungicide sprays and cultivation of resistant potato cultivars are the most effective measures for disease management. The pest introduction in the EU would potentially cause impacts to potato production. The main uncertainties concern the host range, the maximum period the pest survives on host debris in soil, the maximum distance over which conidia of the pest could be dispersed by wind‐blown rain, and the magnitude of potential impacts to the EU. S. andigena meets all the criteria assessed by EFSA for consideration as potential Union quarantine pest. The criteria for considering S. andigena as a potential Union regulated non‐quarantine pest are not met, since the pest is not known to occur in the EU.